2005
DOI: 10.1038/sj.ejhg.5201345
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the ‘critical region’ for cat-like cry of Cri-du-chat syndrome and analysis of candidate genes by quantitative PCR

Abstract: Cri-du-chat (CDC, OMIM 123450) is a chromosomal syndrome that results from partial deletions on the short arm of chromosome 5. The clinical features of CDC normally include high-pitched cat-like cry, mental retardation, microcephaly, hypertelorism and epicanthic folds. The cat-like cry is the most prominent clinical characteristic in newborn children and is usually considered as diagnostic for the CDC syndrome. Using a strategy of 'phenotype dissection', the critical region for cat-like cry was mapped to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 13 publications
(29 reference statements)
1
51
1
7
Order By: Relevance
“…Numerous genetic birth defects have been associated with mutations in RNA modification enzymes, such as the Cri du chat syndrome (NOP2/NOL1/p120/NSUN1) (Wu et al 2005), the Dubowitz syndrome (NSUN2) (Martinez et al 2012), the Noonan-like syndrome (NSUN2) (Fahiminiya et al 2014), or the William-Beuren syndrome (WBSCR20/WBSCR22/ NSUN5) (Doll and Grzeschik 2001). Furthermore, mutations in RNA modification enzymes have also been shown to cause developmental defects, such as Hutchinson-Gilford progeria syndrome (NAT10) (Larrieu et al 2014), and primordial dwarfism (WDR4) (Shaheen et al 2015).…”
Section: Genetic Defectsmentioning
confidence: 99%
“…Numerous genetic birth defects have been associated with mutations in RNA modification enzymes, such as the Cri du chat syndrome (NOP2/NOL1/p120/NSUN1) (Wu et al 2005), the Dubowitz syndrome (NSUN2) (Martinez et al 2012), the Noonan-like syndrome (NSUN2) (Fahiminiya et al 2014), or the William-Beuren syndrome (WBSCR20/WBSCR22/ NSUN5) (Doll and Grzeschik 2001). Furthermore, mutations in RNA modification enzymes have also been shown to cause developmental defects, such as Hutchinson-Gilford progeria syndrome (NAT10) (Larrieu et al 2014), and primordial dwarfism (WDR4) (Shaheen et al 2015).…”
Section: Genetic Defectsmentioning
confidence: 99%
“…The proband in Family III has dysmorphic features, developmental delay, microcephaly, and poor growth, but does not exhibit a cat-like cry. Therefore, the microdeletion in this family does not appear to include the critical region for the cat-like cry in CdCS [Wu et al, 2005]. Recently, Elmakky et al [2014] reported a small terminal deletion (arr[hg19] 5p15.33p15.32(22,178-5,539,182)x1) due to an unbalanced 5;15 chromosomal translocation causing atypical CdCS phenotypes including cat-like cry [Elmakky et al, 2014].…”
Section: Discussionmentioning
confidence: 89%
“…A more severe phenotype and cognitive impairment were reported to be associated with larger deletions [Wilkins et al, 1983;Cornish et al, 1999]. A number of genotypephenotype correlation studies have been performed allowing for definition of critical regions associated with specific manifestations, such as the region for speech delay at band 5p15.3 [Church et al, 1995], the region for cat-like cry between proximal 5p15.3 and distal 5p15.2 [Overhauser et al, 1994;Gersh et al, 1995;Levy et al, 2002;Wu et al, 2005], and the region associated with dysmorphic features at band 5p15.2 [Overhauser et al, 1994;Church et al, 1995;Gersh et al, 1995;Church et al, 1997;Mainardi et al, 2001]. Multiple chromosomal locations have been implicated in intellectual disability and microcephaly, including 5p15.31 [Rossi et al, 2005], 5p15.2, 5p15.1, and 5p13p14 [Overhauser et al, 1994;Gersh et al, 1995;Mainardi et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…CCS is a rare genetic disorder with an estimated incidence between 1:20,000 and 1:50,000 births (Niebuhr, 1978;Wu, Niebuhr, Yang, and Hansen, 2005) and is associated with a partial deletion on the short arm of chromosome 5. The clinical features of CCS include a high-pitched cry in infancy and childhood (Sparks and Hutchinson, 1980;Sohner and Mitchell, 1991), malocclusion, hyperand hypotonia, delayed motor development (Carlin and Fraser, 1990), microcephaly (Niebuhr, 1978), mild-to-profound intellectual disability, including problems with verbal processing (Cornish, Bramble, Munir, and Pigram, 1999), a short attention span, hyperactivity and a stereotypical, aggressive and self-injurious behavioural pattern (Collins and Cornish, 2002).…”
Section: Cri Du Chat Syndromementioning
confidence: 99%